The inclusion of kids with Mental Disability in Kwanza Norte, Angola - Valdmir Francisco Manuel Gamboa (Revista MENDIVE, 2015)
The contemporary world is experiencing an accelerated scientific and technological development in different spheres of social life, playing a leading role in driving the school, which has to improve its educational function of the overall education of current and future generations. It is essential in achieving these aspirations involve teachers, who play a leading role in raising the quality of education, it is necessary to provide teachers with the theoretical and methodological resources, so they can plan and manage efficiently the educational process and comply with comprehensive educational services to students with mental retardation.